An IP-based seamless handover communication architecture for high speed mobile host - Hassan, Md. Mahedi (2011)
With the rapid developments and convergence in the communication and personal computing technology fields, the overall quality of ubiquitous communication has improved significantly. This is especially true with the invention of portable mobile devices that can be connected almost everywhere at any time. However, the recent explosion on the usage of mobile devices, it has also generated several issues in terms of performance and quality of service. Nowadays, mobile users demand high quality performance, best quality of services and seamless connections that support real-time applications such as audio and video streaming. Therefore, in recent years, Network-based Localized Mobility Management working group has proposed a protocol that is actively standardized by the Internet Engineering Task Force which is called Proxy Mobile IPv6 (PMIPv6). PMIPv6 is an effective mobility management protocol for next generation wireless networks that has salient features and is expected to expedite the real deployment of IP mobility management. It has also attracted much attention among the telecommunications and Internet communities. Even though PMIPv6 offers many advantages, it still suffers from lengthy handover latency and huge packet loss. The motivation of this research is to reduce the handover latency and packet loss of mobile host/client during the high speed movement of mobile host. This thesis paper presents a new approach which is a network-based mobility management protocol that aims to reduce the lengthy handover latency, jitter, high packet loss, and increase throughput and the performance of video transmission during the high speed mobility. The proposed approach as a seamless handover integrated solution includes mobility prediction method, a set of Internet Control Message Protocol version 6 messages and effective handover optimization.